brevity design interior spaces (Journal of the College of Basic Education, 2022)
The research consists of the first chapter, which is the importance of the research and its problem, which includesThe next question: What is brevity in the design of interior spaces? The research had two goals and limitsThe objectivity of the design brevity and spatial in the interior spaces, but the temporal boundaries were for the period2- 2014 AD; The term brevity was defined and a procedural definition was put forward for it. Either chThe second is represented by the concept of brevity and expression and its reasons and divisions. as well as allegory and metaphorReferencing and abbreviation. The chapter concluded with the topic of brevity in interior designWith a set of conclusions, the most prominent of which are: brevity works to maintain the design extrapolationWith a coherent and accelerating rhythm with its symbolism for its parts, which includes symbols, metaphors and shorthandThe condenser of meanings and connotations through the shrinking signs in the apparent space form.